2021
DOI: 10.3390/su13073649
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effect of Oil Resources on Environmental Quality: Testing the Environmental Kuznets Curve Hypothesis for Selected African Countries

Abstract: This paper examines the environmental Kuznets curve (EKC) theory, augmenting the role of oil resources and energy consumption in carbon dioxide (CO2) emissions using the annual data of 11 African oil-producing countries from 1980 to 2014. We apply advanced panel cointegration and panel autoregressive distributive lag (ARDL) techniques coupled with Granger non-causality analysis to account for cross-sectional dependence and heterogeneity. The results of the augmented mean group (AMG) reveal that oil resources a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Therefore, the capacity of energy consumption to increase GHG emissions in the European countries is associated with economic activity, as mentioned above. Several authors found this evidence (e.g., Ouédraogo et al [25]; Shahbaz et al [27]; Mendonça et al [72]; Dogan and Inglesi-Lotz [32]; Nawaz et al [73]; Koengkan et al [36]; and Destek et al [37]). Indeed, the increase in economic activity leads to increased energy consumption from non-renewable energy sources.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Therefore, the capacity of energy consumption to increase GHG emissions in the European countries is associated with economic activity, as mentioned above. Several authors found this evidence (e.g., Ouédraogo et al [25]; Shahbaz et al [27]; Mendonça et al [72]; Dogan and Inglesi-Lotz [32]; Nawaz et al [73]; Koengkan et al [36]; and Destek et al [37]). Indeed, the increase in economic activity leads to increased energy consumption from non-renewable energy sources.…”
Section: Discussionmentioning
confidence: 92%
“…The environmental Kuznets curve applied to 11 African countries was investigated by Ouédraogo et al [25]. Considering the causality results using Dumitrescu and Hurlin methodology, this empirical study showed bidirectional causality between CO 2 emission and economic growth.…”
Section: The Relationship Between Energy Consumption and Carbon Dioxi...mentioning
confidence: 96%
See 2 more Smart Citations
“…The threat posed by climate change has intensified interest in the study of economic growth and carbon emissions (CO 2 ). While hydrocarbon fuel reliance and continued carbon emissions have significant effects on the ecosystem and global rising temperatures, sustainable development guarantees the existence of humanity (Ouédraogo et al 2021 ). According to Mesagan and Ekundayo ( 2015 ), a precondition for the attainment of sustainable development as contained in the 2030 global development agenda is for countries to transit to eco-friendly growth and engender an emission-free environment.…”
Section: Introductionmentioning
confidence: 99%